Heavy metal ions removal using amine-functionalized mesoporous adsorbents - Hui Ying, N. (Trans Tech Publications Ltd, 2014)
In the present work, the adsorption of heavy metal ions using amine-functionalized MCM-41 was investigated. Amine-functionalized MCM-41 was synthesized by incorporation of tertiary amine functional group namely 3-2-(2-aminoethylamino) ethylaminopropyltrimethoxysilane (AEPTMS) into MCM-41 through co-condensation method. The resultant adsorbents were characterized using elemental analysis, FTIR, and N2 adsorptiondesorption. Amine-functionalized MCM-41 showed higher Cu2+ adsorption capacity of 4.52 mg/L compared to 0.94 mg/L for MCM-41. Â© 2014 Trans Tech Publications, Switzerland.